REFLECTIONS ON NURSING STUDENTS’ E-LEARNING EXPERIENCES - Hester, Julie; Fakude, Lorraine (Journal of Community and Health Sciences, 2020)
Introduction: To ensure that nursing education stay abreast with modern technology advances has the School of Nursing (SoN) of The University of the Western Cape integrated e-learning into the curriculum. This method articulates well with the case-based approach adopted by the SoN. The Learning Management System, Knowledge Environment for Web-Based Learning (Kewl), Next Generation (KNG), was used to facilitate online teaching and learning. Objectives: The primary aim was to gather baseline data on e-learning by exploring the perceptions and experiences of the first pilot group of undergraduate nursing students who were exposed to this strategy. Methods: A descriptive cross-sectional quantitative design was used to determine the students' understanding and valuing of e-learning, the benefits and skills gained and challenges experienced, by means of a structured, close-ended questionnaire with space for comments. Convenience sampling was used and the questionnaire was distributed to the 87 third year undergraduate nursing students who completed the Primary Mental Health Care module between May and July 2006. Microsoft Excel software was used for the capturing and analysis of the data. Participants: Nursing students in their third year of Baccalaures Curationis degree who participated in the Primary Health Care module. Setting: University of the Western Cape, Cape town. Intervention: Introduction of e-learning as a teaching strategy. Results: The response rate was low. Although some students struggled initially, the majority finally succeeded in mastering e-learning. KNG has benefits but students also face specific challenges that need to be attended to. Most of the respondents felt that the learning experience was valuable and stated that they will recommend it to other students. Conclusion: Students need to adapt to the challenges of modern technology. They still preferred face-to face teaching rather than group work.